MENANAMKAN ENTREPRENEURIAL MINDSET PADA MAHASISWA DAN IMPLIKASINYA DALAM PENDIDIKAN KEWIRAUSAHAAN: STUDI KASUS PADA MAHASISWA PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM DI UIN MAHMUD YUNUS BATUSANGKAR - Deviana Setia Ningrum (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Entrepreneurship education plays a crucial role in fostering entrepreneurship growth in a country. Aside from providing theoretical foundations on entrepreneurial concepts, this education also shapes students' mindset, behavior, and perspectives on entrepreneurship. This research aims to explore the concept of entrepreneurship education, identify the implementation of entrepreneurship education in lectures, and explore factors that can cultivate entrepreneurial interest among students. The research method used is a phenomenological approach with research subjects determined through purposive sampling. Data collection is conducted through observation, documentation, and interviews. Thus, entrepreneurship education is not only about theory but also about shaping the attitudes and skills needed to become successful entrepreneurs. The implications of this research can assist universities in developing more effective and relevant entrepreneurship education programs for students.